Evaluation of Physicochemical Characterization and Elemental Composition of used, Recycled, and Fresh Lubricating Engine Oils of Total Quartz and Hardex Brands - O. V. Akpoveta; S. Opuyor; C. O. Ekwe; Q. Umudi; P. Arogbotimi; H. M. Alajiki (Journal of Applied Sciences and Environmental Management)
Disposal of used engine oils directly into the environment poses severe pollution risk. This can however be checked if green approaches are employed in recycling the waste oil to base oil for further applications. Consequently, the objective of this paper is to evaluate the physicochemical characterization and elemental composition of used, recycled, and fresh lubricating engine oils of Total quartz and Hardex brands using appropriate standard procedures; to ascertain the suitability of the recycled oil for further automobile applications. The recycling process resulted in a 38% recovery of base oil from used Total quartz oil and 42% recovery from used Hardex oil. The examined quality parameters include color, flash point, pour point, carbon residue, specific gravity, ash content, viscosity index, kinematic viscosity, acidic value, total acidic number, and elemental composition (Fe, Cu, Al, Cd, Mn, Zn, Si). A summarized statistical analysis of all the data obtained using ANOVA showed a significant difference at a 95% confidence limit between reference data from fresh oil brands and used oils, indicating significant deterioration of lubricating properties in the used oils. Statistical analysis of quality index data from both recycled oil brands relative to the fresh oil brands showed no significant difference at p<0.05; which demonstrates the success of the green recycling technique. The findings show that the recycled base oil could be rebranded for further applications, therefore a green recycling approach on used engine oils should be encouraged due to its ecological and economic benefits.